2003
DOI: 10.1056/nejm200301163480314
|View full text |Cite
|
Sign up to set email alerts
|

A Serious Adverse Event after Successful Gene Therapy for X-Linked Severe Combined Immunodeficiency

Abstract: We recently reported (April 18 issue) 1 the sustained correction of X-linked severe combined immunodeficiency disease by ex vivo, retrovirally mediated transfer of the g c gene into CD34+ cells in four of five patients with the disease. These results have since been confirmed in four additional patients with typical X-linked severe combined immunodeficiency. Of the first four successfully treated patients, three continue to do well up to 3.6 years after gene therapy, whereas a serious adverse event occurred in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
1,045
1
20

Year Published

2004
2004
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 1,707 publications
(1,069 citation statements)
references
References 4 publications
3
1,045
1
20
Order By: Relevance
“…However, in recent X-SCID gene therapy trials several cases of iatrogenic acute lymphoblastic leukaemia were reported after ex vivo retroviral transduction of the bone marrow cells. 3 Detailed molecular and genetic analyses demonstrated integration of the gammaretroviral genome into the regulatory region of the host LMO2 proto-oncogene, directly implicating the vector in the oncogenic process. 4 Concerns have also been raised by several in vivo studies regarding the possibility of pro-oncogenic events arising from recombinant adeno-associated virus (rAAV) vectormediated gene transfer to hepatocytes, concerns that are supported by vector integration site analyses.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, in recent X-SCID gene therapy trials several cases of iatrogenic acute lymphoblastic leukaemia were reported after ex vivo retroviral transduction of the bone marrow cells. 3 Detailed molecular and genetic analyses demonstrated integration of the gammaretroviral genome into the regulatory region of the host LMO2 proto-oncogene, directly implicating the vector in the oncogenic process. 4 Concerns have also been raised by several in vivo studies regarding the possibility of pro-oncogenic events arising from recombinant adeno-associated virus (rAAV) vectormediated gene transfer to hepatocytes, concerns that are supported by vector integration site analyses.…”
Section: Introductionmentioning
confidence: 99%
“…Duration is also of relevance as the incidences of many human tumours increase substantially with longevity. Notably, even the transformation events that occurred after retroviral gene transfer treatment of X-SCID patients did not result in detectable malignancy until 30 months after treatment, 3 despite the fact that haematopoietic stem cells divide readily and frequently, even in the absence of transformation. Furthermore, the cumulative total number of subjects treated so far in the ophthalmic trials is relatively low.…”
Section: Introductionmentioning
confidence: 99%
“…Next to these tragic events, one of the first success of gene therapy also brought a major tragedy as was reported in 2000 when a group in Paris succeeded in totally correcting Severe Combined Immune Deficiency using a retroviral vector in children, but 2 of the treated children later developed leukemia (49). SCID is characterized by a total lack of T lymphocytes and natural killer cells, which normally defends the body against infections.…”
Section: Safety Issuesmentioning
confidence: 99%
“…They achieved significant levels of immune reconstitution in all but one of the subjects, 5 but the trial had to be suspended when two patients developed leukaemia. 6,7 Concern about the risk of 'insertional oncogenesis' has led to the suspension of other human gene therapy trials using similar vectors to allow for further analysis of the risk-to-benefit ratio.…”
Section: Gene Therapy As a Therapeutic Approachmentioning
confidence: 99%